EFEKTIFITAS LAYANAN INFORMASI TERHADAP PEMAHAMAN MAHASISWA MENGGUNAKAN INTERNET SECARA POSITIF DI PRODI BKI FITK UIN SUMATERA UTARA MEDAN - Khairuddin Tambusai (Universitas Islam Negeri Sumatera Utara Medan, 2018)
Positive behavior is expected to appear in every student activity at school and outside the school. BK lecturers are expected to work together with lecturers of study and all steakholders to shape positive student behavior such as using internet positively. This research uses Quasi experiment type research. The population of the study were students of BKI FITK UIN Sumatera Utara Medan 142, a sample of 32 people. Data collection techniques are questionnaires, data analysis techniques are data descriptions and hypothesis testing. Data analysis was done with the help of SPSS. The results showed: 1) There was a significant difference of understanding scores on students' understanding of using internet positively on experimental group students between test pree with post test. The difference occurred with the increase of the score of all respondents as many as 20 people. Total score increase of 210 with an average increase of 10.50. 2) There was no significant difference in understanding scores about students' understanding using internet positively on control group students between pree test and post test. From 21 respondents only 7 people who experienced an increase. Total increase of 32.50 with an average of 4.64. 3) There is a significant influence of information services on the understanding of students' understanding of using the internet positively on students BKI FITK Students UIN Sumatera Utara Medan Lesson Year 2017/2018 with Asyim sig. 0,000 <0.05.Keywords: Information service, internet use positively